A Cintilografia Cerebral no Diagnóstico dos Tumores - Vieira, Antonio Pinto (2023)
The Cerebral scanning is a very importante method which should be used besides X-Ray examination. It is a simple examination and never produces reactions or any damages to patients. This paper is based in the study of 99 cases, 36 of which were found to be malignant brain tumors. In all our scanning the registration was also done in films. In our opinion the In 113m/(DPTA) gives the same positivity of diagnnosis as the Tc99m.